Correspondence between overweight and socioeconomic and demographic indicators in the adult Brazilian population - Vladimir Schuindt da Silva; Israel Souza; Diego Augusto Santos Silva; Edio Luiz Petroski; Maria de Jesus Mendes da Fonseca (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
OBJECTIVE: To verify the correlation between overweight and socioeconomic and demographic indicators among Brazilian adults, using data from the Brazilian Household Budget Survey from 2008/2009. METHODS: We analyzed the joint relationships between overweight and socioeconomic and demographic indicators in the Brazilian adult population (99,532,672 individuals), through the multiple correspondence analysis technique. RESULTS: The featured profile of the Brazilian adult population with regard to overweight was correlated with ages from 30 years of the most developed and economically social geographic regions of Brazil; however between genders, the correlation was in the opposite direction in the variables income, education, and subjective issues about life conditions related to food and nutrition security. CONCLUSION: By the joint relationship between overweight and selected demographic and socioeconomic indicators, the urgency of the development of strategies and/or preventive public health programs of health problems with overweight in the Brazilian adult population is suggested.